Evaluation of Community Perception on the Adequacy of Infrastructure for the Implementation of the Physics Curriculum Using Davis Process Model among Unity Colleges in North Central Nigeria: Implications on Education for Sustainable Development - Bayo Michael Fadipe (Journal of Education for Sustainable Development Studies, 2025)
This study evaluated community perception on the adequacy of infrastructure for the implementation of the Physics curriculum using the Davis process model among unity colleges in North-Central Nigeria. The study employed a descriptive survey research design. Six thousand four hundred and twenty-nine (6,429) community members across all Unity colleges in North-Central Nigeria make up the study’s population Purposive sampling was employed to select Niger, Nasarawa, and the Federal Capital Territory out of the seven states in North-central, Nigeria. This is because, the states selected shares boundary and have common characteristics. A sample size of 385 community members were randomly selected from the Unity colleges in the three selected states after forming them into strata for used in the study. A researcher-developed questionnaire based on the Davis Process Model was used for data collection. It was validated by three experts. A reliability coefficient of 0.86 was found after the questionnaire underwent a trial test and the data were statistically analysed using the Cronbach Alpha Correlation Formula. Mean and standard deviation was used to answer the research question while Mann-Whitney U-Test was used to test the hypotheses The findings of the study revealed that. Community members perceived that, there is inadequacy of infrastructure for the implementation of the Physics Curriculum based on the Davis Process model. The findings of the study also discovered that, both male and female members of the community perceived that, infrastructure is inadequate for implementing the Physics Curriculum. The findings are threats to Education for Sustainable Development (ESD) this is because, the community perceived inadequacy of the available infrastructure for driving curriculum implementation It was recommended that community members should notify the government and stakeholders on the observed lapses, for immediate action to promote ESD.